معوقات تطبيق ادارة الجودة الشاملة بمؤسسات التعليم التقني والفني : دراسة حالة المعهد العالي لتقنيات شؤون المياه العجيلات - دولة ليبيا - ۲۰۱۸ - عواطف علي عبد السلام موسى,; د. محمد يوسف الشيخ نور, (White Nile Journal for Studies and Research, 2021)
The Study Aimed to certify the obstacles of the application of total quality Management in Technical and Technical Education institutions, for the year ۲۰۱۸ Case Study of the Higher Institute of Water Technology Al-Attila-Suate of Libya. The problem of the Study was: The non-application of educational institutions for the application of total quality Management in accordance with the established scientific principles, represented in the creation of the environment and the appointment of a competent department of total quality, which is one of the most important constraints, and this was evident at the Higher Institute of Water Technologies Ajailat, which reflected negatively in To overcome some of the obstacles and problems that arise daring the evaluation of the educational process in general as quickly as required. The Stady tested two hypotheses there is a statistically significant relationship between the adequate budget for research and development, and the quality of technical and technical Education at the Higher institine of Water Technology, there is a statistically significant relationship between communication and Community service, and the quality of technical and technical Education at the Higher Instinite of Water Technology. The Study used the descriptive method to describe the phenomenon and its variables, the inductive and deductive approach through observation of phenomena and data collection, using SPSS program. Based on the study problem and assumptions, a soft sample was selected for() members of the Study population (3) with 71,12, The Study reached a number of results, including: There is not enough budget for research and development in the Institute, and the Institute is interested in programs that serve the community. As I have reached a member of recommendations, including: The Management of the instituse to pay more attention to programs that serve the community through research, the Management of the instinute to ensare the process of evaluation and development on an ongoing basis in order to make the necessary adjustments and offer ahernatives available in its various activities.